2011
DOI: 10.1037/a0024051
|View full text |Cite
|
Sign up to set email alerts
|

Event-specific drinking among college students.

Abstract: College represents a period of risk for heavy drinking and experiencing unwanted consequences associated with drinking. Previous research has identified specific events including holidays (e.g., New Years), school breaks (e.g., Spring Break) and personally relevant events (e.g., 21st birthdays) that are associated with elevated risk of heavy drinking and negative alcohol-related consequences. The systematic evaluation of relative risk offers insights into event specific drinking and an empirical basis upon whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
108
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 24 publications
3
108
1
Order By: Relevance
“…Some events are associated with particular risk of excessive drinking. Relative to other high-risk drinking events (e.g., New Year's Eve, St Patrick's Day, Cinco de Mayo, Spring Break), 21st birthday drinking has been found to be associated with the highest blood alcohol content (BAC) and proportion of drinkers (5). A study by Rutledge et al (6) found that half of 21st birthday drinkers drank more on this occasion than any other previous occasion.…”
Section: Introductionmentioning
confidence: 97%
“…Some events are associated with particular risk of excessive drinking. Relative to other high-risk drinking events (e.g., New Year's Eve, St Patrick's Day, Cinco de Mayo, Spring Break), 21st birthday drinking has been found to be associated with the highest blood alcohol content (BAC) and proportion of drinkers (5). A study by Rutledge et al (6) found that half of 21st birthday drinkers drank more on this occasion than any other previous occasion.…”
Section: Introductionmentioning
confidence: 97%
“…Perhaps one of the most robust population-level patterns has been the temporal pattern day of the week, as revealed in studies of daily drinking over periods from 3 month (s) up to one year (Del Boca, Darkes, Greenbaum & Goldman, 2004; Neighbors et al, 2011). The relevant studies have highlighted weekends as much more common occasions for drinking than weekdays (Del Boca et al, 2004; Neighbors et al, 2011), irrespective of individual drinking patterns, personality characteristics, and demographics (Hoeppner et al, 2012). Other temporal drinking patterns were reflected in calendar events such as Halloween, New Year's Day, and Spring Break (for college students), which occur on a more intermittent basis.…”
mentioning
confidence: 99%
“…Other temporal drinking patterns were reflected in calendar events such as Halloween, New Year's Day, and Spring Break (for college students), which occur on a more intermittent basis. Such events, along with local holidays, have been shown to be markers of dramatically increased drinking relative to non-holiday weeks (Del Boca et al, 2004; Goldman, Greenbaum, Darkes, Brandon,& Del Boca, 2011) or typical (non-holiday) Saturdays (Neighbors et al, 2011). …”
mentioning
confidence: 99%
“…Celebratory drinking at hazardous levels is well-documented among young adults (e.g., Neighbors et al, 2011). For example, 21 st birthday festivities (e.g., Brister, Sher, & Fromme, 2011; Brister, Wetherill, & Fromme, 2010), holidays and spring break (Glindemann, Wiegand, & Geller, 2007; Lee, Lewis, & Neighbors, 2009), and college football games (e.g., Glassman, Dodd, Sheu, Rienzo, & Wagenaar, 2010; Neal & Fromme, 2007) are associated with young adult celebratory drinking.…”
Section: Introductionmentioning
confidence: 99%